Impact of IT Competency on Organizational Agility With Mediation Role of Absorptive Capacity: Evidence from the Egyptian High Tech Driven SMEs - Khairat, Marwa; Tantawi, Passent; Ragheb, Mohamed A. (The Arab Journal of Administration, 2025)
The purpose of this research is to empirically investigate the relation among IT competency (ITC) and organizational agility (OA)with mediating role of absorptive capacity (AC) in the Egyptian high tech driven SMEs. The objectives of this research are: to investigate how ITC affects OA in the Egyptian high tech driven SMEs, to examine how ITC affects AC in the Egyptian high tech driven SMEs, to identify how AC affects OA in the Egyptian high tech driven SMEs, to test the mediation role of AC in the relationship between ITC and OA in the Egyptian high tech driven SMEs. The study followed the quantitative approach and data gathered from a survey of 419 acceptable responses. The results were analysed employing by structural equation model analyses (SEM) using analysis of a moment structures (AMOS) software. The main conclusions drawn from this study are: the direct effect among ITCand OA is statistically significant, the direct effect among ITCand ACis statistically significant, the direct effect among ACand OA is statistically significant, Finally, ACpartially mediates the relation among ITCand OA. This paper can provide valuable insights into the influence of ITC on OA within an emerging market context. These insights can enrich current understanding which often focuses on developed economies and shed light on how an organization’s ability to learn and adapt from external knowledge sources influences its agility in a dynamic environment. Focusing on the Egyptian High tech driven SMEs. Moreover, the research findings can inform policymakers in Egypt about the importance of fostering IT skills and infrastructure within organizations. This can contribute to creating a more technology-driven and agile business environment for Egyptian companies.